Development of narrow-linewidth diode lasers by use of volume holographic transmission gratings - Ewald, Günter; Kluge, Heinz-Jürgen (Applied physics. B, Lasers and optics, 2005)
We present two diode laser setups that employ volume holographic transmission gratings to provide optical feedback. The advantage of this kind of grating is high diffraction efficiency and the possibility to place optical elements on both sides of the grating. This allows for advanced external cavities and adjustable feedback efficiency. The first setup is a diode laser in the Littman configuration with the transmission grating replacing the conventional reflection grating. The second setup improves the frequency selectivity by substituting the feedback mirror with a passive resonator. This grating-enhanced external cavity diode laser (GECDL) achieves excellent frequency stability. A prototype of the GECDL setup demonstrates an intrinsic linewidth of 7 kHz and an operation range that covers the full amplification profile of the laser diode.